Pengaruh waktu celup dan tegangan listrik terhadap hasil elektroplating bahan baja karbon rendah - Asroni Asroni; Nurlaila Rajabiah; Dien Fahlevi (Universitas Muhammadiyah Metro, 2020)
Electroplating is a process of electro precipitation a metal layer on an electrode which aims to form a surface with different properties or dimensions from the base metal. The metal that is coated is aluminum because it is frequently used as industrial equipment, motor vehicle parts and so on. Low carbon steel is the steel most widely used as a shipbuilding material. As a mode of transportation that operates in corrosive marine environments, a coating protection is needed so that corrosion can be minimized. This study aims to determine the effect of immersion time and electric voltage on the optimal thickness of the electroplating results. Determine the effect of immersion time and electric voltage on the adhesive strength resulting from electroplating. Anode Material coated with ST41 Steel Plate with dimensions of 70 x 25 x 20 mm. while the cathode uses nickel (Ni) with dimensions of 10 x 20 x 20 mm. Cathode to anode distance of 10cm. Dip time 10, 15 and 20 minutes, adhesion testing using PosiTest AT-M Adhesion Tester. The conclusion obtained from this research is that the optimal thickness of the layer is at a voltage variation of 4 volts and immersion time used for 20 minutes with the results obtained of 0.093 mm. While the adhesive strength of the layers from electroplating research was found in the variation of the voltage of 4 volts and the immersion time used for 20 minutes with the results obtained at 21.46 MPa.Keywords: Electroplating, Nickel, anode, cathode, low carbon steel.